Mortality Rate at the Brooding Stage of Various Broiler Breeds Reared in Sub Sahara Region of West Africa - Awobajo, O.K.; Grace, O.; Mako, A.A.; Igbosanun, A.O.; Ettu, R.O. (International Journal of Poultry Science, 2009)
The study was based on morality rate at the brooding stage of various broiler breeds reared in Ogun State, Nigeria. The state was divided into four provinces namely Egba, Egbado, Ijebu and Remo Division. The data were collected through the use of questionnaires, 30 questionnaires were administered in each province making 120 Questionnaires in all. The collective data were analyzed with the use of simple percentage, analysis of variance and other statistic techniques. The result shows that there is significant different (p